Specific cutaneous histologic and immunologic features in a case of early lupus erythematosus scarring alopecia - Ana Maria Abreu Velez; A. Deo Klein; Michael S. Howard (Our Dermatology Online, 2013)
Introduction:Immunoreactants detected by direct immunofluorescence (DIF) in the skin of patients with lupus erythematosus represent an important tool in the diagnosis of this disorder. Case report: A 46 year old African American female presented complaining of hair loss and scarring in her scalp.Methods: Biopsies for hematoxylin and eosin (H&E) examination, as well as for direct immunofluorescence (DIF) were performed.Results: The histologic features were representative of early lupus erythematosus. DIF demonstrated immune deposits of several immunoglobulins and complement, primarily around skin appendageal structures(hair follicles and sweat glands). Deposits of immunoglobulin D were seen in several areas of the epidermis.Conclusion: In lupus erythematosus, evaluation of immune reactions against cutaneous appendageal structures may be crucial in differentiating this disorder from other autoimmune and non-autoimmune diseases.